Respuesta :

Answer:

D

Step-by-step explanation:

Given the root of a quadratic equation x = a then the factor is (x - a)

Here the roots are x = 5 and x = 7 , then the corresponding factors are

(x - 5) , (x - 7)

The equation is then the product of the factors, that is

y = (x - 5)(x - 7) ← expand using FOIL

   = x² - 7x - 5x + 35 ← collect like terms

y = x² - 12x + 35 → D

The quadratic equation has roots of 5 and 7 so, the quadratic equation would be equal to [tex]y = x^{2} - 12x + 35[/tex].

How to find the roots of a quadratic equation?

Suppose that the given quadratic equation is

ax^2 + bx + c = 0

Then its roots are given as:

[tex]x = \dfrac{-b \pm \sqrt{b^2 - 4ac}}{2a}[/tex]

It is Given the root of a quadratic equation x = a then the factor is (x - a)

Here the roots are x = 5 and x = 7 , then the other factors are

(x - 5) , (x - 7)

The equation is then the product of the factors,

[tex]y = (x - 5)(x - 7)\\y = x^{2} - 7x - 5x + 35 \\y = x^{2} - 12x + 35[/tex]

Learn more about finding the solutions of a quadratic equation here:

https://brainly.com/question/3358603

#SPJ2